Gender discrimination in the language classroom - Hariz, Hiba (Beirut Lebanese American University. School of Arts and Sciences, 2009)
Teenage students, who are enrolled in the intermediate classes, are mostly alert of the changes of their bodies. They are sexually aware of the differences between boys and girls physically and mentally and the different reactions they receive form English language teachers regarding their achievement and discipline in class. Boys, for instance, believe that they receive more punishments concerning discipline problems while girls are always the models in the class, for they are always silent and follow all the teachers' roles. On the other hand, teachers consider girls intelligent where it comes to reading, writing, and comprehension while boys are better in grammar, which follows rules; this is why girls get more questions and lower grades in grammar while boys get more inquiries and worse scores in comprehension. The literature has been brought together through looking in library catalogues, computer assisted study exploration, and online investigation. Observations of four teachers in schools were conducted to show how boys and girls are treated differently in the classroom. Then questionnaires were distributed to those teachers and one hundred students to compare the results with what was observed. The results of the study indicated that nearly all lecturers are not alert about the gender bias that is in their classroom, and students, both boys and girls, are facing the problem of uneven treatment from the teachers. The results were compared to the literature review collected and then examined. School administrators should make teachers aware of the problems of gender bias and help overcome the problem for the sake of the students' success. Recommendations on further study directions are suggested.
: Mémoire
Keywords: Enseignement des langues; Gender; Sexe; Teaching languages